The Implementation of Academic Supervision in Improving Teacher Competency at Primary School - Fahmi, Cut Nurul; AR, Murniati; Nurliza, Eli; Usman, Nasir (Jurnal Ilmiah Peuradeun, 2019)
This Study Aims To Obtain The Information And Data Of The Implementation Of Academic In Improving Teacher Competences. The Method Used In This Research Is Descriptive Method With Qualitative Analysis Approach. The Results Showed That: (1) The Education Office And The Supervisors Involved In The Preparation Of Academic Supervision Program By Analyzing The Earlier Programs. The Main Objective Of Academic Supervision Activities Is To Develop Teacher Capacity In Learning Aspects; (2) The Supervision Techniques Include Class Visit, Group Discussion, And Individual Discussion; All Of Which Are Still General; (3) Supporting Factors Include Motivating Teachers To Uphold The Urge And Willingness To Teach And Equipping Them With Various Teaching Methods. The Inhibiting Factors Include The Lack Of Time Allocation For Academic Supervision. A Supervisor Handles Up To 10 Schools. Thus, Not All Teachers Get Utmost Supervision.